Passalora stromatica sp. nov. associated with leaf spots of Tithonia diversifolia in Brazil - Fernandes, Alessandra de F. (International Mycological Association, 2013)
Tithonia diversifolia, a member of Compositae native to Central America that produces showy sunflower-like flowers, became an invasive weed in other continents after it was introduced as an ornamental. Little is known about fungal pathogens infecting this plant. Knowledge of its mycobiota is of interest for future biocontrol programmes for T. diversifolia. In Brazil, a cercosporoid hyphomycete was found associated with intense leaf-spotting of this plant. Based on morphological and molecular data it was recognized as representing a new species of Passalora, and the name Passalora stromatica sp.nov. is introduced here for this taxon. This fungus is described and illustrated herein. It is possible that this fungus is playing a role in Brazil in reducing the invasiveness of T. diversifolia as, contrarily to what has been reported for countries in Africa and Asia, it remains mostly as a garden escape or rural plant in Brazil.